STUDIES ON GENETIC PARAMETERS AND INTER-RELATIONSHIPS AMONG YIELD AND YIELD CONTRIBUTING TRAITS IN PIGEONPEA [CAJANUS CAJAN (L.) MILLSP.] - YOGENDRA PRASAD; KAMLESHWAR KUMAR; S. B. MISHRA (The Bioscan, 2013)
Experiment was conducted on pigeonpea to study the genetic variability, association among the yield component traits, their direct and indirect effects on the yield. Genotypic coefficient of variation was played a major role for the expression of the traits ranged from 1.47 (days to 50 per cent flowering) to 48.13 (grain yield). Heritability in narrow sense ranged from 17.16 (harvest index) to 72.01 (100-seed weight). High genetic advance was observed for the traits, number of primary branches/plant (20.51), number of secondary branches/plant (28.99), leaf area (24.56), number of pods/plant (49.95), pod bearing zone (25.89), pollen viability (62.88) and grain yield (2376.05) coupled with low heritability, indicating the preponderance of the non-additive gene action; suggesting that hybridization breeding will be effective. Number of primary branches/plant (0.345*), number of secondary branches/plant (0.464**), number of pods/plant (0.806**), pod bearing zone (0.433**), harvest index (0.787**) and pollen viability (0.721**) exhibited positive and significant correlation with the grain yield along with their positive and high direct effects ranged from 0.060 to 0.430, suggesting that these traits can be strategically used to improve the yield of pigeonpea.